Differences in the Influence of Core Stability and Balance Training Training on the Risk of Falling in the Elderly - Linda Sahru Ramadani; Dwi kurniawati; Nur Basuki (Politeknik Kesehatan Kemenkes Surakarta, 2023)
Background of the problem: The aging process causes a decrease in the sensory system, musculoskeletal system, and neurological system which will cause balance disorders and also the risk of falling, to reduce these problems, physical activity must be increased, to improve this there are several exercises such as core stability and balance training. Research Objectives: This study aims to determine differences in the effect of core stability training and balance training on reducing the risk of falling in the elderly. Research Methods: The research design was two group pre and post test design. Research Subjects: The subjects in this study were the elderly who were at risk of falling in the Independent Children's Social Service Institution for the Elderly Social Service